The Analysis of In Vivo Aging in Human Bone Marrow Mesenchymal Stromal Cells Using Colony-Forming Unit-Fibroblast Assay and the CD45lowCD271+ Phenotype - Payal Ganguly; Jehan J. El-Jawhari; Agata N. Burska; Frederique Ponchel; Peter V. Giannoudis; Elena A. Jones (Hindawi Limited, 2019)
Uncultured mesenchymal stromal cells (MSCs) are increasingly used in therapies; however, the effects of donor age on their biological characteristics and gene expression remain unclear. The aim of this study was to investigate age-related changes in bone marrow (BM) MSCs following minimal or no culture manipulation. Iliac crest BM was aspirated from 67 healthy donors (19-89 years old) and directly used for the colony-forming unit-fibroblast (CFU-F) assay or CD45lowCD271+ cell enumeration. The colonies were analysed for colony area and integrated density (ID) when grown in standard MSC media or media supplemented with human serum from young (YS) or old (OS) donors. There was a notable age-related decline in the number of MSCs per millilitre of BM aspirate revealed by the CFU-F assay (r=−0.527, p<0.0001) or flow cytometry (r=−0.307, p=0.0116). Compared to young donors (19-40 years old), colony IDs were significantly lower in older donors (61-89 years old), particularly for smaller-sized colonies (42% lower, p<0.01). When cultured in media supplemented with OS, young and old donor MSCs formed colonies with lower IDs, by 21%, p<0.0001, and 27%, p<0.05, respectively, indicating the formation of smaller sparser colonies. No significant differences in the expression of selected adipogenic, osteogenic, stromal, and bone remodelling genes as well as CD295, CD146, CD106, and connexin 43 surface molecules were found in sorted CD45lowCD271+ MSCs from young and old donors (n=8 donors each). Altogether, these results show similar trends for age-related decline in BM MSC numbers measured by the CFU-F assay and flow cytometry and reveal age-related effects of human serum on MSC colony formation. No significant differences in selected gene expression in uncultured CD45lowCD271+ MSCs suggest that old donor MSCs may not be inferior in regard to their multipotential functions. Due to large donor-to-donor variation in all donor groups, our data indicate that an individual's chronological age is not a reliable predictor of their MSC number or potency.